Influence of the precipitation temperature on the thrust force and torque in drilling an Al 2219-SiCpsub composite - Ganesh, Radhakrishnan (Materiali in tehnologije, 2014)
This paper aims at understanding the influence of the precipitation temperature on the drilling performance of an Al 2219-SiC composite. This type of composite is currently in use in aerospace industries. Drilling is the most frequently employed secondary machining owing to the requirements of the fabrication. This composite was subjected to the precipitation heat treatment, hence calling for a study of the precipitation-temperature effect on the machining performance. The composite was fabricated through the powder-metallurgy route. The drilling trials were conducted with a PCD drill of a 5 mm diameter and 118° point angle. The experiments were conducted with different spindle speeds of (500, 1000 and 1500) r/min and feed rates of (10, 15 and 20) mm/min. The thrust force and torque were the performance indicators. The influences of the mass fraction of reinforcement, the precipitation temperature, the feed rate and the spindle speed on the thrust force and torque during drilling were analyzed. It was observed that the drilling performance was influenced significantly by the feed rate followed by the precipitation temperature, the mass fraction and the particle size of reinforcement. The spindle speed did not influence much the machining performance.
Keywords: powder metallurgy; praškovna metalurgija; composites; kompoziti; drilling; izločevalno žarjenje; temperature; vrtanje; temperatura